2018
DOI: 10.1155/2018/2907572
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Investigation of Combustion and Heat Transfer Characteristics of Oscillating Linear Engine Alternator

Abstract: An Oscillating Linear Engine Alternator (OLEA) has the potential to overcome the thermal, mechanical, and combustion inadequacies encountered by the conventional slider-crank engines. The linear engines convert the reciprocating piston motion into electricity, thereby eliminating needless crankshaft linkages and rotational motion. As the dead center positions are not explicitly identified unlike crankshaft engines, the linear engine exhibits different stroke and compression ratio every cycle and should manage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…It is based on a twostroke, gas-fuelled, spark-ignited single-cylinder engine assisted by a mechanical spring as a rebound device. The results indicated that an increase in spring stiffness from 50 to 350 kN/m improved the system operating frequency by 18% and power output by 12% under constant compression ratio, while the system efficiency decreased by 2%, which was attributed to the decrease of charging efficiency (EGR ratio increased by 12%) under the conditions of constant intake/exhaust and high frictional loss (4%) [13,14].…”
Section: Fpeg Simulation and Experimental Researchmentioning
confidence: 99%
“…It is based on a twostroke, gas-fuelled, spark-ignited single-cylinder engine assisted by a mechanical spring as a rebound device. The results indicated that an increase in spring stiffness from 50 to 350 kN/m improved the system operating frequency by 18% and power output by 12% under constant compression ratio, while the system efficiency decreased by 2%, which was attributed to the decrease of charging efficiency (EGR ratio increased by 12%) under the conditions of constant intake/exhaust and high frictional loss (4%) [13,14].…”
Section: Fpeg Simulation and Experimental Researchmentioning
confidence: 99%
“…The Clark group of West Virginia University investigated the operation characteristics and the piston and engine performance of a single-cylinder-type FPELG and a dualcylinder-type FPELG coupled with a mechanical spring on the basis of simulation results and experimental results [8][9][10]. It was found that the operation frequency of the piston and the power of the free piston engine are positively correlated with the spring stiffness, while the efficiency decreased with the increase in spring stiffness [11].…”
Section: Single-cylinder/single-piston Fpelg Structure Type Coupled W...mentioning
confidence: 99%
“…Moreover, the combustion characteristics of the FPELG coupling with the mechanical spring were also simulated, and the results demonstrated that the combustion starting timing advanced, the adverse work and heat transfer both increased, while the overall efficiency declined [15]. Yingcong Zhou from Stony Brook University researched The Clark group of West Virginia University investigated the operation characteristics and the piston and engine performance of a single-cylinder-type FPELG and a dual-cylindertype FPELG coupled with a mechanical spring on the basis of simulation results and experimental results [8][9][10]. It was found that the operation frequency of the piston and the power of the free piston engine are positively correlated with the spring stiffness, while the efficiency decreased with the increase in spring stiffness [11].…”
Section: Single-cylinder/single-piston Fpelg Structure Type Coupled W...mentioning
confidence: 99%
“…Chen-Zhao et al [9] studied the fluid flow and heat transfer characteristics in the pipe cable with alternating current by using commercial code COMSOL Multiphysics based on the finite element method. Bade et al [10] used the MATLAB/Simulink numerical model of a single cylinder, mechanical spring assisted, two-stroke natural gas fueled, spark-ignited oscillating linear engine alternator to investigate the effect of combustion and heat transfer characteristics on translator dynamics and performance. Dou, Jiang, and Zhang [11] investigated the thermal flow and heat transfer by natural convection in a cavity fixed with a fin array.…”
Section: Literature Reviewmentioning
confidence: 99%